E-Service Quality, Corporate Image, Government Policy terhadap E-Satisfaction pada Universitas yang di Moderasi E-Trust - Albetris Albetris; M Alhudhori; Reni Devita; Muhammad Emil (J-MAS (Jurnal Manajemen dan Sains), 2022)
Service competition at the University with the use of technological facilities to serve people who have not been served by services at the University has great potential to expand the distribution of services to the community. The model of service marketing, relational marketing and digital marketing needs to be studied simultaneously through a service marketing management approach to get e-satisfaction. The purpose of this study was to obtain an e-Satisfaction model at the University as a marketing strategy for University services, especially in Jambi Province. The research design used an explanatory survey approach. The survey was conducted at Private Universities in Jambi Province. The number of respondents as many as 392 University service users taken by random sampling. Data analysis was carried out using a structural equation modeling (SEM) approach and the SmartPLS 4 program.